1995
DOI: 10.1002/ijc.2910600524
|View full text |Cite
|
Sign up to set email alerts
|

E‐selectin expression induced by pancreas‐carcinoma‐derived interleukin‐1α results in enhanced adhesion of pancreas‐carcinoma cells to endothelial cells

Abstract: Cellular adhesion of sialyl-Lewis-a(SLea)-positive pancreas carcinoma to endothelial cells (EC) is augmented by activation of EC via up-regulated E-selectin expression on EC. Co-cultivation of pancreas-carcinoma cells, PCI-24, with human umbilical-vein endothelial cells (HUVEC) for 5 hr at the PCI-to-HUVEC ratio of 1:10 induced E-selectin expression on the endothelial-cell surface, augmenting SLea-positive pancreas-carcinoma cell attachment with HUVEC. Culture supernatants of 6 tested pancreas-carcinoma cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 11 publications
1
30
0
Order By: Relevance
“…In contrast to most other adhesion molecules, selectin functions were initially thought to be restricted to leukocyte interaction with the vascular endothelium (Kaltner and Stierstorfer, 1998;Tedder et al, 1995;Vestweber and Blanks, 1999). However, several studies have demonstrated that selectins can act as homing receptors at the lumenal surface of the microvascular endothelium for tumor cells and that hematogenous metastasis of cancer involves recognition of tumor cell surface sugar epitopes, ie, sialylated Lewis epitopes, by selectins, thereby facilitating tumor cell arrest and transmigration into the extravascular space (Biancone et al, 1996;Brodt et al, 1997;Kaji et al, 1995;Kannagi, 1997;Nakamori et al, 1993;Tozeren et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to most other adhesion molecules, selectin functions were initially thought to be restricted to leukocyte interaction with the vascular endothelium (Kaltner and Stierstorfer, 1998;Tedder et al, 1995;Vestweber and Blanks, 1999). However, several studies have demonstrated that selectins can act as homing receptors at the lumenal surface of the microvascular endothelium for tumor cells and that hematogenous metastasis of cancer involves recognition of tumor cell surface sugar epitopes, ie, sialylated Lewis epitopes, by selectins, thereby facilitating tumor cell arrest and transmigration into the extravascular space (Biancone et al, 1996;Brodt et al, 1997;Kaji et al, 1995;Kannagi, 1997;Nakamori et al, 1993;Tozeren et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Several cell types could be the source of these cytokines. These include tumor cells (Kaji et al, 1995), endothelial cells responding to tumor cell-induced vascular damage (Orr et al, 1988) or resident Kupffer cells (Hoffman et al, 1994) and circulating platelets (Hakamori, 1994), which may be mobilized in response to the influx of tumor cells (or a combination of the above). In this manner, the local inflammatory response, in fact, may contribute to increased arrest of mechanically trapped or circulating tumor cells in the liver microvasculature.…”
Section: Discussionmentioning
confidence: 99%
“…3) (13,54-56). Kaji et al (54) and Khatib et al (55) showed that upon entry into the hepatic circulation, epithelial tumor cells can rapidly trigger a molecular cascade (involving interleukin-1 secretion by tumor cells) leading to the induction of E-selectin expression on the sinusoidal endothelium (Fig. 3).…”
Section: Inhibition Of Cancer Cell Migration and The Development Of Lmentioning
confidence: 99%